A validation of the non-parametric continous norming procedures - Siy, Melissa Jane
Abstract (The aim of the study is to analyze and validate the statistical aspect of the non-parametric continuous norming technique, which is a method used in creating scores in psychometric tests. Using the Work Profile Questionnaire-Emotional Intelligence (WPQei) with Filipino used to create age-group-based scores (age norms). Based on the results, the models from the technique can produce useable scores in practice with acceptable adjusted R-squared values; however, some challenges emerged with regards to the process of choosing the smoothing parameter, consistency of the significant variables and coefficient signs of the model, and the calculation of the score tables. Bootstrapping is recommended in improving the robustness of the technique).
October 2017.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Non-Parametric continous norming procedure